Biochemical and nutritional characteristics of some commercial banana (Musa spp.) cultivars of Kerala - Thatayaone, Malikongwa; Saji, Gomez; Meagle , Joseph; Netravati; Kuruvila, Bintu (Plant Science Today, 2022)
Biochemical and nutritional traits of 6 banana (Musa spp.) cultivars commercially cultivated in Kerala, belonging to different genomic groups viz. Pisang Lilin (AA), Grand Naine (ABB), Nendran (AAB), Karpooravalli (ABB), Njalipoovan (AB) and Yangambi (KM-5) (AAA) were evaluated. Biochemical and nutritional characters on variables such as titratable acidity (%), total soluble solids (oBrix) (TSS), total protein (g), total carbohydrates (g), total fat (%), total ash (%), crude fibre (%), vitamin C (mg), calcium (mg), potassium (mg), total phenols (mg) and total carotenoid (µg) content were laid out in a completely randomized design and subjected to one way ANOVA to determine the significance (p=.05). The cultivar Nendran (AAB) exhibited desirable biochemical and nutritional traits, particularly for titratable acidity (0.34%), TSS (23.90oB), total carbohydrates (37.51g/100g), total ash (14.89%) and crude fibre (0.90%) content. Yangambi (KM-5) (AAA) exhibited the highest values for major minerals of banana, especially calcium (168.90 mg/100g) and potassium (406.60 mg/100g). The current study reveals biochemical and nutritional variation among banana cultivars from different genomic groups, with similarities and differences overlapping even among banana cultivars from the same genomic group.